2009
DOI: 10.1590/s0102-86502009000500009
|View full text |Cite
|
Sign up to set email alerts
|

Study on the vaginal smear of rats submitted to autologous ovarian transplant: impact of remote ischemic preconditioning

Abstract: Purpose:To evaluate the remote ischemic preconditioning (R-IPC) impact on the quality of the ovarian graft by means of vaginal smear of transplanted rats. Methods: Sixty rats were used divided in six groups: Control; Fresh transplant (TxF); Cryopreserved transplant (TxC); R-IPC; R-IPC + fresh transplant (TxF+R-IPC); R-IPC + cryopreserved transplant (TxC+R-IPC). R-IPC was performed in the common iliac artery. Autologous ovarian tissue was implanted integrally in the retro peritoneum. On the first PO day, vagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…As our study indicated, the number of follicles in the autografted groups compared with the control groups decreased considerably, which confirms previous reports [23,24]. This could be explained because in the first days of transplantation, granulosa cells and oocytes, particularly in developing follicles, undergo apoptosis as a result of ischemia and reperfusion injury induced by free radicals and lipid peroxidation.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…As our study indicated, the number of follicles in the autografted groups compared with the control groups decreased considerably, which confirms previous reports [23,24]. This could be explained because in the first days of transplantation, granulosa cells and oocytes, particularly in developing follicles, undergo apoptosis as a result of ischemia and reperfusion injury induced by free radicals and lipid peroxidation.…”
supporting
confidence: 90%
“…R-IPC leads to earlier re-initiation of ovarian activity and increases the number of cycles in fresh graft, which can be related to a compensatory effect after I/R injury during the transplant when growth factors are produced to establish graft angiogenesis. The established neovascularization may stimulate the graft to re-initiate its function [23] which justifies the findings.…”
supporting
confidence: 77%
“…The subsequent transplantation is considered as an alternative treatment to restore fertility in cancer female patients who are at risk of ovarian failure after deleterious effects of cancer therapy [2] [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…While earlier studies have considered that the major loss of viable follicles quantity occurred after transplantation rather than freeze-thaw procedure because transplantation directly related to time duration for re-establishing of blood supply to graft tissues [5] [8].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of reproductive capacity has been long neglected by researchers [7][8][9][10] . Over the last few years, scientific advances have permitted the occurrence of pregnancy in cases of ovariectomy by means of various methods, such as ovarian cryopreservation, ovarian follicle transplantation, ovarian implants and others 11 .…”
Section: Introductionmentioning
confidence: 99%